PENGARUH PEMBERIAN EKSTRAK KUNYIT PUTIH (Curcuma zedoaria) DAN TEMULAWAK (Curcuma xanthorrhiza) DALAM AIR MINUM TERHADAP PRODUKTIVITAS BROILER - Loraya, Karel; Malle, Dominggus; Wattiheluw, Muhammad Juraid (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study was conducted to determine the effect of giving white turmeric extract (Curcuma zedoaria) and temulawak (Curcuma xanthorrhiza) in drinking water on broiler productivity. Broilers, white turmeric and temulawak were used in this study with 4 treatments and 4 treatments in a completely randomized design. The results of the study revealed that the administration of white turmeric and temulawak extracts in drinking water on broiler productivity had no significant effect, namely Feed consumption P0: 763.14 g / head / week, P1: 787.92 g / head / week, P2: 759.3, P3: 765.60 g / head / week, Drinking water consumption P0: 1833.65 mL / head / week, P1: 1819.69 mL / head / week, P2: 1747.74 mL / head / week, P3: 1825.40 mL / head / week, Body Weight Gain P0: 489.38 g / head / week, P1: 495.67 g / head / week, P2: 487.17 g / head / week, P3: 482.92g/head/week. Feed conversion P0: 1.53, P1: 1.55, P2: 1.52, P3: 1.54 and Feed efficiency P0: 0.67, P1: 0.67, P2: 0.68, P3: 0.66. Although statistically this study did not indicate any significant difference, but physically there was a difference.